2018
DOI: 10.1016/j.eswa.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Time series for early churn detection: Using similarity based classification for dynamic networks

Abstract: The success of retention campaigns in fast-moving and saturated markets, such as the telecommunication industry, often depends on accurately predicting potential churners. Being able to identify certain behavioral patterns that lead to churn is important, because it allows the organization to make arrangements for retention in a timely manner. Moreover, previous research has shown that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The literature highlights a great diversity of ML and data mining techniques for CCP. Among these are Decision tree, Logistic regression and Random forests (De Caigny et al, 2018;Höppner, Stripling, Baesens, & Verdonck, 2017;Nisha, 2016), Support vector machine (Dong, Suen, & Krzyzak, 2005;Farquad, Ravi, & Raju, 2014;He, Shi, Wan, & Zhao, 2014;Renjith, 2017;Wang, Zhang, & Yu, n.d.), Active learning (Jamil & Khan, 2016;Verbeke, Martens, Mues, & Baesens, 2011), Rough set theory (Amin et al, 2016;Amin, Anwar, Adnan, Khan, & Iqbal, 2015), Negative correlation learning (Rodan, Fayyoumi, Faris, Alsakran, & Al-Kadi, 2015), Dynamic networks (Óskarsdóttir, Van Calster, Baesens, Lemahieu, & Vanthienen, 2018), AdaBoost ensemble techniques (Idris et al, 2017), Sequential pattern mining (Culbert et al, 2018), Recursive PARTioning (RPART) (Vafeiadis et al, 2015) Artificial neural network (Kasiran, Ibrahim, Syahir, & Ribuan, 2014;Tsai & Lu, 2009;Zakaryazad & Duman, 2016). The aforementioned discussion shown the importance of CCP as it is very beneficial assets of competitive businesses and equally important for various domain, such as; Banking sector (Chitra & Subashini, 2011;He et al, 2014;Oyeniyi & Adeyemo, 2015), Financial services (Charles et al, 2017;He et al, 2014), Social networks (Maria, Verbeke, Sarraute, Baesens, & Vanthienen, 2016;Óskarsdóttir et al, 2017;Verbeke, Martens, & Baesens, 2014), Online gaming industry (Kawale, Pal, & Srivastava, 2009;Suznjevic, Stupar, & Matijasevic, 2011), Human resource man-agement (Sarad...…”
Section: Customer Churn and Ccp Modelingmentioning
confidence: 99%
“…The literature highlights a great diversity of ML and data mining techniques for CCP. Among these are Decision tree, Logistic regression and Random forests (De Caigny et al, 2018;Höppner, Stripling, Baesens, & Verdonck, 2017;Nisha, 2016), Support vector machine (Dong, Suen, & Krzyzak, 2005;Farquad, Ravi, & Raju, 2014;He, Shi, Wan, & Zhao, 2014;Renjith, 2017;Wang, Zhang, & Yu, n.d.), Active learning (Jamil & Khan, 2016;Verbeke, Martens, Mues, & Baesens, 2011), Rough set theory (Amin et al, 2016;Amin, Anwar, Adnan, Khan, & Iqbal, 2015), Negative correlation learning (Rodan, Fayyoumi, Faris, Alsakran, & Al-Kadi, 2015), Dynamic networks (Óskarsdóttir, Van Calster, Baesens, Lemahieu, & Vanthienen, 2018), AdaBoost ensemble techniques (Idris et al, 2017), Sequential pattern mining (Culbert et al, 2018), Recursive PARTioning (RPART) (Vafeiadis et al, 2015) Artificial neural network (Kasiran, Ibrahim, Syahir, & Ribuan, 2014;Tsai & Lu, 2009;Zakaryazad & Duman, 2016). The aforementioned discussion shown the importance of CCP as it is very beneficial assets of competitive businesses and equally important for various domain, such as; Banking sector (Chitra & Subashini, 2011;He et al, 2014;Oyeniyi & Adeyemo, 2015), Financial services (Charles et al, 2017;He et al, 2014), Social networks (Maria, Verbeke, Sarraute, Baesens, & Vanthienen, 2016;Óskarsdóttir et al, 2017;Verbeke, Martens, & Baesens, 2014), Online gaming industry (Kawale, Pal, & Srivastava, 2009;Suznjevic, Stupar, & Matijasevic, 2011), Human resource man-agement (Sarad...…”
Section: Customer Churn and Ccp Modelingmentioning
confidence: 99%
“…Computational results show that it is somehow related to the relationship of each customer with other banks. Inspired by Óskarsdóttir et al [ 10 ], it would be interesting to better understand the motivations to churn, including “social contagion”.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the referenced work consider applications in the telecommunication sector (see, for instance, [ 10 15 ]). Applications of churn prediction methods in other sectors can also be found.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that there is an influence among customers' relationships and their churn decision (Óskarsdóttir, Van Calster, Baesens, Lemahieu, & Vanthienen, 2018), as far as we know, centrality metrics over temporal graphs have not been applied over telco customers in the context of churn prediction.…”
Section: Social Network Analysis For Churn Predictionmentioning
confidence: 99%